Investigative (search) and covert investigative (search) actions as means of proof in criminal proceedings related to illegal trafficking in firearms or ammunition - S. V. Kozachenko (Bulletin of Kharkiv National University of Internal Affairs)
The subject matter of the study is to provide a detailed description of investigative (search) and covert investigative (search) actions as means of proof in criminal proceedings related to illegal trafficking in firearms or ammunition. The purpose of the article is to clarify the place, content, significance and system of such actions.